Body talk : 37 voices explore our radical anatomy - Jensen, Kelly (2020)
"Thirty-seven contributors-including model Tyra Banks, gymnast Aly Raisman, and bestselling YA authors-explore the world in their unique bodies through essays, lists, comics, and art, from the award-winning editor of (Don't) Call Me Crazy"--
Includes bibliographical references
Ages 14 and up
Grades 10-12
Keywords: Human body -- Social aspects -- Juvenile literature; Human body -- Political aspects -- Juvenile literature; Body image -- Juvenile literature; Juvenile works; Juvenile works